Graph Modeling for the Sustainability of Da'wa Communication Platforms in the Digital Information Society - Pamuji, Agus; Muzaki (Proceedings of International Conference on Da'wa and Communication, 2022)
The role of information technology is very important in building communication relations between users in cyberspace. The relationship of digital communication with platforms through social media is very complicated. The most important thing is the pattern of communication in the spread of da’wa in cyberspace. Currently, the form of cyber media is only used for the use and evaluation of how da’wa can adopt internet media. In this paper, our motivation is to make data modeling on communication patterns with digital platforms through social media in the dissemination and development of da’wa media. The research method is starting with the collection, extraction, understanding of data, the formation of a graph model and the evaluation stage. The modeling is in the form of a graph using network-based analysis techniques through the identification of entities and also relationships with other entities. The final result of this discussion is that the graph model is measured by the centrality method to ensure the validity of the model. Based on the results of tests and evaluations with centrality that graph modeling is considered very good for modeling communication by building a classification of media forms used.